Politik Hukum Pidana dan Keadilan bagi Masyarakat dalam Penegakan Tindak Pidana melalui Keadilan Restoratif - Finsensius Samara; Gabriel Seran; Hendrik Dami; Agnes Pareira (Jurnal Hukum Lex Generalis, 2025)
This paper analyzes the gap between legal idealism and reality in Indonesian criminal law enforcement, which often favors retributive practices over substantive justice. Using a normative juridical approach, the study highlights the strategic shift toward restorative justice as reflected in Law No. 1 of 2023. However, fundamental obstacles regarding substance, structure, and culture persist. Consequently, legal reform must focus on harmonizing regulations and transforming law enforcers' mindsets to establish criminal law as an ultimum remedium, thereby ensuring responsive social justice.